PROVIDING PSYCHOLOGICAL AND PEDAGOGICAL SUPPORT TO PARTICIPANTS OF THE EDUCATIONAL PROCESS IN THE CONDITIONS OF MILITARY ACTIONS - Vergolyas , Maya; Vergolyas , Oleksandr; Verholias , Olexander (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
The military events taking place in Ukraine are stressful for all participants in the educational process. In these conditions, the role of psychological services in the education system, which ensure timely and systematic provision of psychological and social pedagogical support to all participants in the educational process in accordance with the goals and objectives of the education system, is significantly increased. It is very important to provide a psychologically comfortable educational environment for all students, to ensure a quality educational process for children with psychological trauma, to give teachers the opportunity to work with children with psychological trauma, to provide support for teachers and to involve parents in the educational process. Developing a psychological support strategy will help reduce the negative impact of stress and promote the recovery of children's psyche and ability for effective learning and development.